2015
DOI: 10.1039/c5tb00226e
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a novel blended membrane with chitosan and silk microfibers for wound healing: characterization, in vitro and in vivo studies

Abstract: Pure chitosan membranes present insufficient mechanical properties and a high swelling ratio, which limits their application in biomedical field. In this study, silk microfibers were obtained by chemical hydrolysis, and a novel type of chitosan/silk microfiber (CS/mSF) blended membrane was reported and its multiple physical properties were evaluated. The mechanical properties were significantly improved after blending silk microfibers with a chitosan matrix, while the swelling ratio was decreased. Observation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 50 publications
0
50
0
Order By: Relevance
“…HA (150 kDa) was purchased from Lifecore Biomedical (US). [41,42] Briefly, 10 g cut pieces of silk cocoons were boiled for 30 min in 1 L of 0.5 wt% Na 2 CO 3 solution followed by rinsing thoroughly with distilled water to degum SF. 3-(Acrylamido-1hydroxypropane-1,1-diyl) bis(phosphonic acid) was prepared according to our previous report.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…HA (150 kDa) was purchased from Lifecore Biomedical (US). [41,42] Briefly, 10 g cut pieces of silk cocoons were boiled for 30 min in 1 L of 0.5 wt% Na 2 CO 3 solution followed by rinsing thoroughly with distilled water to degum SF. 3-(Acrylamido-1hydroxypropane-1,1-diyl) bis(phosphonic acid) was prepared according to our previous report.…”
Section: Methodsmentioning
confidence: 99%
“…mSF with 200-300 µm length and around 10 µm diameter ( Figure S1, Supporting Information) were directly obtained from macroscopic silk fibers using a "top-down" method according to our previous reports [41,42] Inorganic coating of the surface of mSF was accomplished through biomineralization, i.e., by immersing the microfibers in 1.5 × simulated body fluid (SBF) for 7 d (Figure 1). Fourier transform infrared spectroscopy (FTIR) was used to identify the molecular structure of the CaP@mSF and mSF (Figure 2a).…”
Section: Msf Preparation and Cap Coatingmentioning
confidence: 99%
“…Mechanical properties, such as the tensile strength and elongation at break are usually considered crucial for various biomaterials, which could provide the biomaterials with sufficient tension and strength in clinical application especially when it is used as wound dressing at the joints, ankles or elbows . Table shows us the significant impacts of various crosslinking methods on the mechanical properties of PADM.…”
Section: Resultsmentioning
confidence: 99%
“…1518 Because of its superior and tunable mechanical properties, controllable degradation and relatively low inflammatory response, SF has been used to replace collagen, and blended with chitosan (CS), a biocompatible natural biomaterial with some similarities with glycosaminoglycan, to mimic the ECM composition. 4 Although many previous studies suggested better biocompatibility with silk rather than CS materials, 19,20 better biocompatibility and cell growth in vitro and in vivo than pure silk and CS were achieved using SF-CS composite scaffolds, by tuning the ratio of SF and CS, suggesting that they have promising applications as matrices. 2123 …”
Section: Introductionmentioning
confidence: 99%